Niche shift in three foraging insectivorous birds in lowland Malaysian forest patches - Mansor, Mohammad Saiful; Nor, Shukor Md; Ramli, Rosli; Sah, Shahrul Anuar Mohd (Elsevier, 2018)
With the rapid growth of agricultural areas globally, forest birds increasingly encounter fragmented landscapes in which forest patches are surrounded by an agricultural plantation matrix, yet how birds respond behaviourally to this fragmentation is poorly understood. Information on microhabitat requirements of birds is scarce, but nevertheless essential to predicting adaptation of bird species to the patchy landscapes. We investigated foraging patterns of three tropical insectivorous birds, Green Iora Aegithina viridissima, Pin-striped Tit-Babbler Macronus gularis and Chestnut-winged Babbler Cyanoderma erythropterum, to determine whether they vary in foraging methods in different forest patches. Our study area encompassed old-logged lowland forest; one continuous forest and three forest patches. Observations were performed for 15 days every month for a period of 13 months. Information on foraging height, substrate, attack manoeuvres, and foliage density was collected independently for each foraging bird individual. All three species used different foraging substrates and attack manoeuvres in different habitat types. The Green Iora frequently used lower strata when foraging in forest patches as opposed to continuous forest, while the Pin-striped Tit-Babbler tended to forage in more dense vegetation in patches. Only Chestnut-winged Babbler displayed complete foraging plasticity across all study parameters. Different habitat features (e.g., edges, microclimates) between continuous forest and forest patches significantly influenced the foraging strategies of the study species. These changes in foraging strategies suggest that some Malaysian forest birds (e.g. generalist species) can respond behaviourally to fragmentation and habitat loss. Although continuous forest has critically important characteristics that need to be conserved, remnant forest patches are also important as ecological movement corridors and foraging grounds for birds.